Who nose what eye can see? : examining the impact of scent on visual attention - Chong, Trinetta Chiao Sing. (2012)
Extant literature has shown that sensory cues, such as scent, affect how visual and visuo motor tasks are carried out. While many cross-modal studies have explored the interactions between olfactory and visual cues, little research has examined the effects of scent on visual attention specifically. Our research aimed to determine whether scents can enhance visual attention towards congruent stimuli in the context of an advertisement. 148 participants were recruited for three studies, where their visual attention (i.e. frequency and duration of eye fixation) was recorded using an eye tracking system. In Study One, subjects in the treatment condition were asked to view a series of print advertisements in the presence of a scent. The print ads contained pictorial or textual cues that were either congruent or incongruent to the scent. Results showed that visual attention towards a pictorial or textual cue was significantly greater when it was congruent to the scent accompanying the ad. In Studies Two and Three, color perceptions and semantic associations of scent were explored. Findings revealed that visual attention towards a pictorial or textual cue was also significantly increased when it was either ‘color congruent’ or semantically congruent with the scent. Our collective findings demonstrate an olfactory priming effect on visual selective attention, where a scent can enhance visual attention towards specific cues in an advertisement if they are directly or semantically congruent with the scent. Implications of the findings for advertisers and marketers are discussed.